On control of direct-drive permanent magnet synchronous machines in micromobility applications - Gül, Kürşad Metehan (Graduate School, 2023)
In micromobility applications with direct drive powertrain configuration, the traction torque and speed are directly generated by a Surface-mount Permanent Magnet Synchronous Machine (SPMSM), and no other transmission components are utilized, thus the operating region in which the motor must reliably operate is excessively wide. Hence, maintaining satisfactory motor control performance in that wide torque-speed envelope of an SPMSM is a challenge due to the increasing nonlinearities outside the nominal operating region. This thesis deals with the design and analysis of reliable and high-performance motor control systems for direct-driven micromobility SPMSMs. Throughout this thesis, a motor control system is designed for direct-driven SPMSMs to establish high-performance and reliable motor control operation on micromobility platforms. To achieve robust and satisfactory speed control of SPMSM by maintaining reliability, the design and tuning parameters selection of voltage feedback field weakening vector control structure with Cascaded PI (CPI) is explained. A special emphasis is put on the implementation issues and environmental disturbances, thus several existing nonlinear phenomena that must be considered in the control system design are experimentally analyzed. Also, the designed CPI structure is tested and validated through both conducted computer simulations and experimental tests. As demonstrated in the conducted experimental voltage ripple analysis, the voltage ripple amplifications due to the cascaded control structure of CPI impose a limit on the speed control loop bandwidth in CPI, thus its speed control performance can only be improved to a certain degree in practical applications. Therefore, a novel Fuzzy-Linear Quadratic Regulator (F-LQR) is designed in which the error compensation dynamics of the baseline LQR is manipulated through a Fuzzy Logic Controller (FLC) to improve the speed control performance in the transient state while maintaining the optimality in the steady state. Due to its state-feedback type MIMO control structure, improving the speed control performance in the novel F-LQR does not increase the voltage ripples. Also, a geometrical characterization strategy is adopted when shaping the fuzzy mapping of the FLC in which the desired characteristic manipulation in F-LQR is achieved. The designed CPI and F-LQR control systems are comparatively analyzed by conducting experimental tests on the real-world test setup under two compelling scenarios to assess speed control and voltage ripple performances under excessive torque loading and successive reference tracking conditions. The comparative experimental results revealed that the F-LQR outperformed LQR and CPI controllers in terms of both reference tracking and disturbance rejection. Also, a discussion to highlight the pros and cons of these two different control structures is provided from a micromobility traction application point of view. To improve control system robustness and reliability while reducing production costs, two different sensorless speed and position estimation algorithms i.e., Extended State Observer with Phase Locked Loop (ESO-PLL) and back-EMF observer with PLL (EMF-PLL) are developed. A hall-effect sensor-based position estimation strategy is also presented to obtain position information in standstill and critically low-speed operating regions. To achieve reliable and accurate estimations of rotor speed and position under disruptive internal and external disturbances, a proper selection of tuning parameters of the designed observers is also given. The speed and position estimation performances of the designed observers are comparatively analyzed by conducting computer simulations and experimental tests on the real-world test setup. Three different realistic test scenarios are applied in which the abrupt accelerating/ decelerating, successive reference tracking including field weakening region, and excessive torque loading conditions are investigated. The results of the conducted computer simulations and experimental tests revealed the advantages of the EMF-PLL observer over the ESO-PLL and Hall-based methods in all operating regions of the SPMSM.
Mikromobilite uygulamalarında kullanılan direkt sürüşlü kalıcı mıknatıslı senkron makinelerin kontrolü üzerine
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Micromobility; Mikromobilite; Synchronous machines; Senkron makineler